PENGARUH KARAKTERISTIK INDIVIDU DAN ETOS KERJA TERHADAP EFEKTIVITAS PENYELESAIAN PERKARA PADA SATUAN RESKRIM POLRES JEMBRANA - LATIF, MUH. WAHYUDIN (Kerta Dyatmika, 2015)
ABSTRAKThe main task of the police is to maintain public order and law enforcement. Affirmation of special police powers in performing police duties governed by Article 2 of Law No. 2 of 2002 on the Indonesian National Police. Police must act professionally and holds the code of conduct strictly and hard, so it is not easy to fall to the hated spectrum of society. On behalf of the law, the police were given greater authority. In fact, this authority is not given to any institution to force even curb freedoms and human rights, among others, capture, detain, search, seize, ordered to stop, prohibit people leave the place, checking the identity of a specific person. The main problem in this paper is "whether there is the influence of individual characteristics and work ethic of the effectiveness of settling disputes in the Criminal Police Unit Jembrana?" While the sub subject matter is whether there is the influence of individual characteristics on the effectiveness of the settlement ?, whether there is an influence on the effectiveness of the completion of the work ethic ?, matter whether there is influence of individual characteristics and work ethic of the effectiveness of the settlement?The approach used is quantitative and survey method. Population and sample of 58 people who are members of the Criminal Police Unit Jembrana. Data collection techniques using questionnaires. Data were analyzed using the research instrument test (validity and reliability), the classic assumption test and test hypotheses.Based on the research findings and discussion, it can be concluded; (a) The effect of the individual characteristics are significant to the effectiveness of settling disputes; (b) the work ethic is a significant influence on the effectiveness of settling disputes; (c) the effect of individual characteristics and work ethic is simultaneously significantly to the effectiveness of the settlement.As for suggestions - suggestions put forward by the authors of the research that has been conducted, among others; 1) is recommended in order to provide reinforcement to the work ethic Jembrana Criminal Police Unit members so that members do not feel compelled to carry out his duties and uphold every job he is performing; 2) suggested that is always committed to provide the best performance with consummate quality management overall (total quality service) to carry out their duties with full responsibility in the discipline works.Â Keywords: individual characteristics, work ethic, the effectiveness of the settlement.